Critical velocity relationship to ventilatory gas exchange parameters and maximal lactase steady state in swimming - Espada, Mário (2018)
Trabalho apresentado em 22nd Annual Congress of the European College of Sport Science, 5-8 de julho 2017, Bochum, Alemanha